China’s Development in Two Decades After Reform - Ridha Amalia; Syuryansyah Syuryansyah (Social Science Research Journal, 2024)
China‘s development cannot be denied as a remarkable success since open and reform policy took place in 1978. China has shifted from a centrally-planned to a market- based Economy and has experienced rapid economic and social development. GDP growth has averaged nearly 10 percent a year—the fastest sustained expansion by a major economy in history. During two decades of its reform, numerous policies were implemented in China such as Household Responsibility System (HSR), Township and Village Enterprises (TVEs), and Special Economic Zones (SEZs). These policies have been critical for China‘s rapid development. As China's economic grow, China becomes one of the countries with an economic model that can serve as an example for others. But can a similar development model be applied to another country? This paper tries to examine the developments happening in China during two decades of its reform if it is particular or universal?